Prospects for prevention of HPV-driven oropharynx cancer - Kreimer, Aimée R. (Oral oncology, 2014)
Prevention of HPV-associated cancers can take two forms—one through prevention of infection via prophylactic HPV vaccination, and one through interruption of disease progression through early identification (i.e.: screening) and treatment. Primary prevention via vaccination seems promising, as a proof-of-principal study demonstrated high vaccine efficacy against one-time detection of oral HPV16/18 infection. In addition to the direct benefit of vaccination, indirect protection from reduced genital HPV infection should also reduce oral HPV exposure at the individual level. Yet, for the current unvaccinated cohorts who will bear the burden of non-cervical HPV-associated cancers for the foreseeable future, no secondary prevention opportunities exist, as the field has not yet validated any screening methods for non-cervical HPV associated cancers. Serum HPV16 E6 antibody data suggest that this test might one day be able to detect many of the at-risk patients prior to tumor development. For any biomarker that proves valid and reliable, transitioning into clinical practice will require additional research focused on (1) diagnostics, (2) effective intervention, and (3) observed reductions in cancer mortality.